Sustained Exposure to Helicobacter pylori Lysate Inhibits Apoptosis and Autophagy of Gastric Epithelial Cells - He, Yang; Wang, Cunlong; Zhang, Xiulin; Lu, Xuancheng; Xing, Jin; Lv, Jianyi; Guo, Meng; Huo, Xueyun; Liu, Xin; Lu, Jing; Du, Xiaoyan; Li, Changlong; et al. (Frontiers in Oncology, 2020)
Abstract Helicobacter pylori (H. pylori) is designated as a class I carcinogen of human gastric cancer after a long-term infection. During this process, H. pylori persists in proliferation and death, releases bacterial components, which contact with gastric epithelial cells and regulate cell function. However, the long-term treatment of H. pylori lysate in the pathological changes of gastric cells is not clear. In this study, GES-1 and MKN-45 cells were treated with H. pylori lysate for 30 generations, and cells proliferation, migration, invasion, autophagy and apoptosis were detected to determine the regulation of cell by continuous exposure to lysate. Furthermore, Mongolian gerbils were infected by H. pylori ATCC 43504 strains for 90 weeks to verify the results in vitro. We found that sustained exposure to H. pylori lysate inhibited host cells invasion, migration, autophagy and apoptosis. The clinical data and in vitro showed that the expression changes of Nod1, NF-κB, MAPK/ERK and FOXO pathways and the downstream genes related to apoptosis and autophagy. Sustained exposure to H. pylori lysate inhibited cells apoptosis and autophagy through Nod1-NF-κB/MAPK-ERK/FOXO4 signaling pathway. In conclusion, sustained exposure to H. pylori lysate promoted proliferation of gastric epithelial cells and inhibited autophagy and apoptosis through Nod1-NF-κB/MAPK-ERK/FOXO4 signaling pathway.